Exposure to multiple pathogens: Serological evidence for Rift Valley fever virus, Coxiella burnetii, Bluetongue virus and Brucella spp. in cattle, sheep and goat in Mali - Dione, Michel M.; Séry, A.; Sidibé, C.A.K.; Wieland, Barbara; Fall, Abdou (2022)
An important problem for livestock production in Mali is occurrence of several infectious diseases. A particular challenge for control of pathogens that affect different species, especially in a system with mixed herds with cattle, sheep and goats. Therefore, this study aimed to investigate co-exposure with Rift Valley fever virus (RVFV), Coxiella burnetii, bluetongue virus (BTV) and Brucella spp. in different livestock species in mixed herds. With the exception of BTV these pathogens are also zoonotic. A retrospective assessment was carried out on a biobank of sera of cattle and small ruminants collected from Sikasso and Mopti regions. Nine hundred and twelve samples from cattle (n = 304), sheep (n = 318) and goat (n = 290) were screened. Serology tests were conducted using commercial kits as per the protocol of the manufacturers. Sero-prevalence for RVFV was 12.8% (Confidence Interval 95%: 9.3–17.1%); 4.7% (2.7–7.7%) and 3.1% (1.4–5.8%) in cattle, sheep and goat respectively. For Coxiella burnetii, the sero-prevalence was 55.3% (49.5–60.9%), 22.6% (18.2–27.6%), and 16.9% (12.8–21.7%); in cattle, sheep and goat respectively; and for BTV sero-prevalence was 88.8% (84.72–92.13%), 51.6% (45.9–57.2%), 56.2% (50.3–62.0%) in cattle, sheep in goat respectively. Brucella sp. had the lowest sero-prevalence and was only detected in cattle and sheep. Regional differences were observed with sero-prevalence of Coxiella burnetii in sheep and goat and BTV in goat being significantly higher in Sikasso than in Mopti (p<0.001). Evidence of exposure to two pathogens in the same animal was most common for the combination Coxiella burnetii and BTV in cattle (51.6%), followed by sheep (17.0%) and goat (15.5%). Considering the scarcity of disease occurrence and epidemiological data in most sub-Saharan countries including Mali, this multi-pathogen survey provides important evidence that cattle, sheep and goat are exposed to pathogens that may negatively impact productivity and pose a risk for public health. The results from this study highlight the urgent need for a better understanding of pathogen diversity and their impact on human and animal health in order to minimize resulting risks. Given that some of the pathogens investigated here are zoonotic, establishment of One-Health surveillance system to monitor disease in animals and people is warranted and intersectoral collaboration is recommended.